The Impact of Arginine Side Chains on the Mechanism of Polycondensation of Silicic Acid in Bioinspired Mineralization - Jose Lanuza; Enrico Ravera (Inorganics)
The polycondensation of silica from soluble silicic acid is at the basis of several chemical processes. The usual industrial route requires harsh pH conditions and high concentrations of the precursor molecules, not to mention a thermal treatment for obtaining condensed structures. On the other hand, biological organisms can promote the precipitation of silica under physiological conditions, including temperature and pH, and low concentrations of precursors. The key to this process is the use of polycationic molecules. Despite the relevance of these processes in modern industrial inorganic chemistry, this fascinating process is still not completely understood. Recent studies converge in pointing out that the role of the polycation is to create supersaturation of silicic acid in its immediate proximity, which would explain the impact of the polycation on the reaction rates. However, it remains unclear whether these polycations also directly influence the reaction mechanism at a molecular level. In this manuscript, we address this question by analyzing the reaction pathway of silicic acid dimerization in the presence of guanidinium as a mimic of the arginine side chain, through DFT calculations. We found that the impact on the reaction pathway is minimal, which strengthens the hypothesis of the local supersaturation driven by the polycationic molecules.